What happens during a teaching-learning process of martial arts and combat sports with novice – A case-study focused on the joint activity organization analysis (Revista de Artes Marciales Asiáticas, 2019)
Semiotic devices are relevant tools to study the teaching-learning process according to the constructivist perspective, which supports several of the game-centered approach models. Even not being included in the generality of these models, martial arts and combat sports have a clear potential to be developed according to these models. Following this, it was settled a didactic sequence based on the fighting knowledge development through the learning of a striking and a throwing skill. A pragmatic discourse analysis was made and specific forms of joint activity organization, called segments of interactivity, were identified. Inside these segments, several patterns were registered considering their main function and format of interaction. The segments of interactivity of activity organization and guided practice constituted both the bigger part of the time and total number of segments, which suggest that the learning processes should be understood inside of their scope. This way, looking for the activity organization, the predominance of the patterns related with “execution” evolve according with the appropriation of the contents, while the “function” patterns seem to be more relevant when it is proposed a new or more complex task. By the other hand, the results related to guided practice segments remark the importance of the one-to-one interactions between the teacher and the apprentice within the whole classes situation. These results show the singularity of every teaching-learning process in terms of the progressive transfer of control and responsibility from the teacher to the apprentice and the simultaneous establishment of an increasingly rich network of shared meanings between these agents.